Development of renewable energy resources by green finance, volatility and risk: Empirical evidence from China. (December 2022) - Lin, Chia-Yang; Chau, Ka Yin; Tran, Trung Kien; Sadiq, Muhammad; Van, Le; Hien Phan, Thi Thu
Abstract: Green finance and investment in renewable energy (RE) sources are two of the most important climate change strategies that might have a long-term impact. Micro- and macro-level data from 2010 to 2021 in China used to gain a new analysis of the impact of green finance, inflationary pressures, and geopolitical risk in improving sustainability. Regression estimation methods were used to tackle this while considering direct and indirect associations between the parameter estimates. According to recent research, environmental taxes, such as those on carbon emissions, have been shown to have a large and favorable effect on profitability in RES. The volatility of oil prices and geopolitical risk, on the other hand, has a negative influence on the investment pattern for sustainable energy sources in China. The research also shows that green rules have a significant role in reducing the impact of green finance on RE production. Green companies in China should be pushed so that RE investments are regarded as a long-term strategy, according to the conclusions of the research. The study's theoretically, and empirically conclusions have supplied policymakers and environmentalists with useful information for developing and implementing environmental initiatives with long-term financial benefits. Highlights: This study focused solely on the economic and environmental consequences of renewable energy sector in China. Green rules have a tempering effect while enhancing the association between green finance and renewable energy expenditure. Renewable energy greatly benefits from green funding.